Effect of Types of Nutrients and Several Varieties of Kale (Brassica Oleracea Var. Palmifolia) on Growth and Production - Samudi samudi; Ratna Dewi Mulyaningtiyas; Sadam Husin (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
Hydroponic cultivation is one technique for increasing food production on a small piece of land. Nutrient utilization in hydroponic cultivation needs to be cautious in order to sustain plant growth. Plant growth is significantly influenced by the type of fertilizers used. Knowing the right kinds of nutrients to employ and the suitable plant varieties is essential when growing kale since, in addition to utilizing nutrients, plant varieties also influence how much is produced during the growth process. The location of the research was the Green House Pokmas Parasku Hijau, Paras Hamlet Rt.01/Rw.02, Banjarejo Village, Ngadiluwih District, Kediri, East Java 64171. The research took place from December 2021 to January 2022, lasting two months (60 days), and it used a completely randomized design with two components and three replications (r-1). The first factor or main plot is the nutrient concentration, which has three trademark versions (N) and a 5 ml/liter value. These versions are N1 (goodplant brand mix), N2 (Flo brand blend), and N3 (high grade brand blend). The second plot point or element is made up of the three Kale variety (K) levels: K1 (green kale), K2 (red Russian), and K3 (curly kale). Based on results, the growth and productivity of kale were not significantly impacted by ABmix nutrients or other kale cultivars. When used to treat different types of nutrition, ABmix Premium Grade nutrition has the best impact on the development and production of kale plants. The best-growing kale varieties, however, when treated, were the curly and green varieties.